A new species of the genus Mygdonia (Hemiptera: Heteroptera: Coreidae) from Madagascar with a key to species - Baňař, Petr; Brailovsky, Harry; Hubáčková, Lenka; Hemala, Vladimír (Zootaxa, 2014)
A new species, Mygdonia milivoji sp. nov. (Coreidae: Coreinae: Mictini) from south-west Madagascar is described, illustrated and compared with widely distributed M. elongata Distant, 1879. A key to Mygdonia species based on females is given and distribution of both Madagascan species is briefly discussed.